PENGARUH IKLAN TOKO ONLINE, HARGA, ONLINE CUSTOMER REVIEWS TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO PINTU BAJA JAYA 99 DI MARKETPLACE - Yudhea Vanestius; Widjaja, William (Jurnal Nusa Manajemen, 2025)
This study aims to analyze the influence of online advertising, price, and online customer reviews on consumers purchase intention at Pintu Baja Jaya 99 Store. The research employs a quantitative approach using a survey method through questionnaires distributed to 109 respondents. The data were analyzed using multiple linear regression. The results show that simultaneously, online advertising, price, and customer reviews have a significant effect on purchase intention. Partially, online advertising and online customer reviews have a significant influence, while price does not significantly affect purchase intention. These findings indicate that consumers tend to consider online advertising and customer reviews more when deciding to purchase products online. Therefore, business owners are advised to manage attractive online store advertisements and pay attention to online reputation through customer reviews in order to increase consumer purchase intention.